All-optical switch exploiting Fano resonance and subwavelength light confinement - Saudan Quentin; Bekele Dagmawi A.; Xiong Meng; Yvind Kresten; Galili Michael; Mørk Jesper (Nanophotonics)
We propose and experimentally demonstrate a small-mode volume bowtie cavity design for all-optical switching applications using a waveguide-cavity structure that exploits asymmetric Fano resonance lineshapes. The bowtie cavity has a mode volume that is five times smaller than conventional (H0-type) photonic crystal point-defect cavities enabling higher nonlinearity and faster switching. Blue and red-detuned Fano resonant devices based on bowtie cavity designs have been fabricated and characterized. Measured linear transmission spectra have been compared to coupled-mode theory models to extract key parameters such as Q-factors. Furthermore, all-optical switching at 2.5 Gbps have been demonstrated in a wavelength-conversion experiment.